Conservation Zone Delimitation Based on Physical Properties in Langsa Watershed, Aceh Province - Faiz Urfan; Ayu Sekar Ningrum (Geosfera Indonesia, 2022)
Watershed zoning is essential for regional development, specifically the conservation aspect. Langsa is a city in Aceh province that has no watershed zoning map as a basis for development. Therefore, this study aims to delimit the conservation area in the Langsa River Basin, Aceh Province, based on three factors, which include rainfall, slope, and vegetation density. The data used are Digital Elevation Models (DEM), Langsa City rainfall, and satellite imagery from Landsat 8 OLI TIRS. Furthermore, the data was obtained online from the website of Badan Informasi Geospasial also known as Geospatial Information Agency, the United States Geological Survey, and Badan Pusat Statistik or Central Bureau of Statistics. The data was processed using the Quantum GIS 3.16 application with scoring and weighted overlay. In this study, the Langsa watershed was divided into three areas, namely cultivation, buffer, and conservation. The cultivation area dominates the Langsa watershed with a sloping morphology, moderate rainfall, and moderate vegetation density. Also, the conservation area has a high morphology with high rainfall and vegetation density, while that of the buffer has characteristics that falls between the cultivation and conservation areas. Each zone namely cultivation, buffer, and conservation has respective areas of 63.75 km2, 4.84 km2, and 3.55 km2 with different land use priorities. For example, the cultivation zones are prioritized for agricultural and urban areas. Buffer is separated for perennials, while conservation zones are for protected forests or national parks. Keywords : Langsa Watershed; Conservation Area; Buffer Area; Cultivation Area Copyright (c) 2022 Geosfera Indonesia and Department of Geography Education, University of Jember This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License